Fiqh for Minority (Fiqh al-Aqalliyyāt): Principle and Current Practice on Food and Mortgage Finance - El Ashfahany, Afief; Apriantoro, Muhamad Subhi; Maruf, Aminudin (Suhuf: International Journal of Islamic Studies, 2025)
This paper examines Fiqh al-Aqalliyyat (Fiqh for Minorities), focusing on food and mortgage finance, and questions whether the principle of darurah (necessity) central to this jurisprudence remains valid today. Through library-based research, it analyzes foundational concepts primarily drawn from Yusuf al-Qaradawi’s work and contrasts them with contemporary realities. Over two decades since Fiqh al-Aqalliyyat emerged in 2003, halal food accessibility and Islamic finance options remain limited for Muslim minorities in non-Muslim-majority countries. While the fiqh offers legal concessions (rukhsah), it does not absolve Muslims of their duty to conduct muamalah (transactions) in line with Sharia. The study argues that establishing halal infrastructure and Sharia-compliant financial systems is a fard kifayah, a communal obligation. Neglecting this duty implicates the entire community in shared sin. Thus, the paper urges Muslim minorities to move beyond reliance on concessions and actively build halal alternatives. At minimum, raising awareness about halal standards and Islamic finance is an essential collective responsibility. This serves as a timely reminder that necessity should not become complacency.